2012
DOI: 10.1186/1471-2350-13-118
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lung cancer risk in a Chinese population using a multifactorial genetic model

Abstract: BackgroundLung cancer is a complex polygenic disease. Although recent genome-wide association (GWA) studies have identified multiple susceptibility loci for lung cancer, most of these variants have not been validated in a Chinese population. In this study, we investigated whether a genetic risk score combining multiple.MethodsFive single-nucleotide polymorphisms (SNPs) identified in previous GWA or large cohort studies were genotyped in 5068 Chinese case–control subjects. The genetic risk score (GRS) based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 30 publications
3
37
1
Order By: Relevance
“…Similar observations for G allele and/or GG genotype of hTERT 2736100 T>G polymorphism was reported for ALL (Sheng et al, 2013), ovarian cancer (Terry et al, 2012), cervical cancer (Wang et al, 2012) and bladder cancer (Gago-Dominguez et al, 2011). Our results are in line with previous findings displaying that there was an association between the G allele and/or GG genotype of hTERT 2736100 T>G polymorphism and increased risk for various cancers (Sheng et al, 2013;Li et al, 2013;Lan et al, 2013;Myneni et al, 2013;Li et al, 2012;Wang et al, 2010;Chen et al, 2011;Peng et al, 2015;Terry et al, 2012;Wang et al, 2012;Gago-Dominguez et al, 2011). On the contrary to these results, Shadrina et al (2015), Ding et al (2011), andJannuzzi et al (2015) reported that there was no correlation between hTERT 2736100 T>G polymorphism and susceptibility to BC, hepatocellular carcinoma and CRC, respectively.…”
Section: Accepted Manuscriptsupporting
confidence: 95%
See 2 more Smart Citations
“…Similar observations for G allele and/or GG genotype of hTERT 2736100 T>G polymorphism was reported for ALL (Sheng et al, 2013), ovarian cancer (Terry et al, 2012), cervical cancer (Wang et al, 2012) and bladder cancer (Gago-Dominguez et al, 2011). Our results are in line with previous findings displaying that there was an association between the G allele and/or GG genotype of hTERT 2736100 T>G polymorphism and increased risk for various cancers (Sheng et al, 2013;Li et al, 2013;Lan et al, 2013;Myneni et al, 2013;Li et al, 2012;Wang et al, 2010;Chen et al, 2011;Peng et al, 2015;Terry et al, 2012;Wang et al, 2012;Gago-Dominguez et al, 2011). On the contrary to these results, Shadrina et al (2015), Ding et al (2011), andJannuzzi et al (2015) reported that there was no correlation between hTERT 2736100 T>G polymorphism and susceptibility to BC, hepatocellular carcinoma and CRC, respectively.…”
Section: Accepted Manuscriptsupporting
confidence: 95%
“…Regarding to hTERT rs2736100 T>G polymorphism, results of case-control studies and metaanalysis of these studies were also reported with controversial (Sheng et al, 2013;Shadrina et al, 2015;Jannuzzi et al, 2015;Li et al, 2013;Lan et al, 2013;Myneni et al, 2013;Li et al, 2012;Wang et al, 2010;Chen et al, 2011;Peng et al, 2015;Terry et al, 2012;Wang et al, 2012;Gago-Dominguez et al, 2011;Ding et al, 2011). For instance, there are numerous investigations focused on the relation between hTERT rs2736100 T>G polymorphism and LC risk (Lan et al, 2013;Myneni et al, 2013;Li et al, 2012;Wang et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 83%
See 1 more Smart Citation
“…The Etzel model is for African-Americans, and the Li and Park models apply to Chinese and Korean men, respectively. [77][78][79] Maisonneuve presented two models. The first is a version of the Bach model recalibrated in an Italian population for identifying those at high risk who would be suitable for screening; the second model uses initial screening results so is not applicable for pre-screening use.…”
Section: Specific Risk Prediction Modelsmentioning
confidence: 99%
“…When externally validated using CARET data, however, discrimination was modest (AUC, 0.68). Similarly, others have extended existing models or developed new models to incorporate candidate single nucleotide polymorphisms (SNPs) associated with lung cancer [25, 3641]. Improvements in risk prediction were consistently modest, although at most 20 SNPs were incorporated in a single model.…”
Section: Predicting Lung Cancer Risk Prior To Screening Initiationmentioning
confidence: 99%